Răspuns :
a+b+c=198 | *2
b-c=123 |*(-1)
2a+2b+2c=396
-b+c=-123
le adunam
2a+2b+2c-b+c 396-123
2a+b+3c=273
b-c=123 |*(-1)
2a+2b+2c=396
-b+c=-123
le adunam
2a+2b+2c-b+c 396-123
2a+b+3c=273
a+b+c=198
b-c=123⇒b=123+c
inlocuim b astfel obtinut in prima ecuatie
a+123+c+c=198
a+2c=198-123
a+2c=75
2a+b+3c=?
adunam prima ecuatie cu ultima ecuatie obtinuta, membru cu membru
(a+b+c)+(a+2c)=198+75
⇒
2a+b+3c=273
b-c=123⇒b=123+c
inlocuim b astfel obtinut in prima ecuatie
a+123+c+c=198
a+2c=198-123
a+2c=75
2a+b+3c=?
adunam prima ecuatie cu ultima ecuatie obtinuta, membru cu membru
(a+b+c)+(a+2c)=198+75
⇒
2a+b+3c=273